Statistical Analysis of Traffic Accidents in Shanghai River Crossing Tunnels and Safety Countermeasures. (4th February 2014) - Lu, Linjun; Lu, Jian; Xing, Yingying; Wang, Chen; Pan, Fuquan
Abstract : A large number of traffic tunnel accidents have been reported in China since the 21th century. However, few studies have been reported to analyze traffic accidents that have occurred in urban road tunnels. This study aims to examine the characteristics of the temporal, spatial, and modality distributions of traffic in Shanghai river crossing tunnels using statistical analysis and comparative analysis. Employing these techniques tunnel accident data obtained from Shanghai center 110 was analyzed to determine temporal and spatial distribution characteristics of traffic accidents in river crossing tunnels in Shanghai. The results of this analysis are discussed and summarized in this paper. Identification of the characteristics of tunnel traffic accidents can provide valuable information for development of effective countermeasures to improve tunnel safety in China.